Highly reactive α-bromoacrylate monomers and Michael acceptors obtained by Cu(ii)Br2-dibromination of acrylates and instantaneous E2 by a ligand. Issue 16 (3rd April 2018) - Moreno, Adrian; Lejnieks, Jānis; Ding, Liang; Grama, Silvia; Galià, Marina; Lligadas, Gerard; Percec, Virgil
Abstract : The importance of the order of addition of reagents in SET-LRP. Abstract : Depending on the order of their addition to the reaction mixture, acrylates can undergo SET-LRP or dibromination by Cu(ii )Br2 and spontaneously dehydrohalogenate to provide the corresponding highly reactive α-bromoacrylate monomer and Michael acceptor.